KEBIJAKAN PEMERINTAHAN JOKOWI TERKAIT TENAGA KERJA INDONESIA DI MALAYSIA DAN IMPLIKASINYA TERHADAP HUBUNGAN DUA NEGARA SERUMPUN - Ali Maksum (The Indonesian Islamic Studies and International Relations Association (Insiera), 2017)
In 2014 Indonesian Presidential Election, Joko Widodo promised to give a priority in the issue of Indonesian migrant workers, especially in Malaysia. This was basically part of Jokowi’s program to protect Indonesian citizens abroad. In Malaysia, Indonesian migrant workers have involved into various problems and cases. Therefore, this article attempts to examine Jokowi’s administration related to Indonesian migrant workers in Malaysia and its impact to both countries bilateral relations. Both countries obviously gained many advantages from the influx of Indonesian migrant workers in Malaysia. The migrant workers remittance is one of the largest revenue for Indonesian government. As for Malaysia, the presence of Indonesian migrant workers highly contributed to the national economy amid lack of interest of Malaysian citizens to such kind of “dirty jobs.” Hence, this article invites readers into the comprehensive discussion on migrant workers issue and Indonesia-Malaysia relations, especially during the first half of Jokowi’s tenure of the office.